A case report of nonsurgical idiopathic normal pressure hydrocephalus differentiated from Alzheimer's dementia: Levetiracetam was effective in symptomatic epilepsy. Issue 3 (2nd September 2022) - Ishida, Tetsuro; Murayama, Tomonori; Kobayashi, Seiju
Abstract: Background: Idiopathic normal pressure hydrocephalus (iNPH) is a common form of dementia that causes gait disturbance, cognitive impairment, and urinary incontinence. iNPH is a "treatable dementia" that can be treated with shunt surgery, but this can be ineffective in some cases and can be accompanied by complications. As a result, many patients with iNPH do not undergo surgery. However, there is insufficient evidence on effective treatments other than surgical therapy. Case Presentation: A 75‐year‐old woman presented to our hospital with a chief complaint of cognitive decline. She showed reduced motivation and inactivity. Brain magnetic resonance imaging showed a high score on the Evans Index (maximum width between bilateral lateral ventricular anterior horns/maximum intracranial cavity in the same slice). The subarachnoid space was enlarged at and below the Sylvian fissure, and narrowed at the higher arcuate region. She was diagnosed with iNPH. However, no shunt surgery was performed; 11 months later, she had a generalized convulsive seizure with loss of consciousness. An electroencephalogram showed generalized epileptic discharges. The possibility of surgery for her iNPH was ruled out. Levetiracetam prevented seizure recurrence and cognitive functions such as spontaneity and motivation were improved. Conclusion: It is often assumed that surgery is the only effective treatment for patients with iNPH. However, as in the present case, symptomatic epileptic seizures may be a factor in dementia. Even in the absence of surgical treatment, we should examine the cause of dementia in patients with iNPH and consider pharmacological treatment, including antiepileptic drugs. Abstract : The disease course and treatment of patients with nonsurgical idiopathic normal pressure hydrocephalus is not clear. However, such patients must be differentiated from other dementias, such as Alzheimer's dementia. They also require medication and support in the psychiatric field.